Inhibition of RANKL Expression in Osteocyte-like Differentiated Tumor Cells in Giant Cell Tumor of Bone After Denosumab Treatment. (March 2023) - Noguchi, Takashi; Sakamoto, Akio; Murotani, Yoshiki; Murata, Koichi; Hirata, Masahiro; Yamada, Yosuke; Toguchida, Junya; Matsuda, Shuichi
Giant cell tumors of bone (GCTBs) are locally aggressive tumors with the histological features of giant cells and stromal cells. Denosumab is a human monoclonal antibody that binds to the cytokine receptor activator of nuclear factor–kappa B ligand (RANKL). RANKL inhibition blocks tumor-induced osteoclastogenesis, and survival, and is used to treat unresectable GCTBs. Denosumab treatment induces osteogenic differentiation of GCTB cells. In this study, the expression of RANKL, special AT-rich sequence-binding protein 2 (SATB2, a marker of osteoblast differentiation), and sclerostin/SOST (a marker of mature osteocytes) was analyzed before and after treatment with denosumab in six cases of GCTB. Denosumab therapy was administered a mean of five times over a mean 93.5-day period. Before denosumab treatment, RANKL expression was observed in one of six cases. After denosumab therapy, spindle-like cells devoid of giant cell aggregation were RANKL-positive in four of six cases. Bone matrix–embedded osteocyte markers were observed, although RANKL was not expressed. Osteocyte-like cells were confirmed to have mutations, as identified using mutation-specific antibodies. Our study results suggest that treatment of GCTBs with denosumab results in osteoblast–osteocyte differentiation. Denosumab played a role in the suppression of tumor activity via inhibition of the RANK–RANKL pathway, which triggers osteoclast precursors to differentiate into osteoclasts.